Prevalence of uterine lesions associated with leiomyomas and role of endometrial biopsy in management - Kumbhalwar, Minal J.; Konda, Anuradha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Present study highlights association between symptomatic patients of fibroids and its coexistence with pathologies like endometriosis, adenomyosis, polyp, endometrial hyperplasia and carcinoma. The aim was evaluating role of endometrial biopsy before surgery. Methods: The study was observational cohort, conducted on women operated for fibroid or recently diagnosed with fibroid. 150 women were included. Histopathology reports of already operated were analysed for association between uterine pathology and fibroid. In prospective cases ultrasonography findings was noted and patients having leiomyoma underwent biopsy and reports studied for association. Chi-square test done to find association between qualitative variable and p value <0.05 considered significant. Results: Out of 150, 24.6% had adenomyosis, 14% had endometrial hyperplasia in which 2% had atypia and 12% without atypia, 8.6% had cervical polyp, 5.33% had endometrial polyp, 4% had endometriosis while 42.7% had no association. Conclusions: This study revealed increasing trend of coexistence of leiomyomas with uterine pathologies. Early identification of endometrial pathologies on clinical history and imaging helps in selection of high-risk patients who need biopsy to rule out malignancy thus avoiding routine D and C which is done for every case.